THE ABANDONMENT OF RURAL OLD TOWNS: MORATALLA, MURCIA - López Sánchez, Pascual Augusto; Medrano, Fco. José Sánchez; Pérez, Joaquín J. Pastor (Advances in Social Sciences Research Journal, 2017)
The demographic problem is one of the most troubling issues in today’s society. The tendency of human concentration in big cities promotes the continuing exodus of rural communities what, added to the deficit of services and amenities of our old towns, leads to a situation of progressive abandonment. The current need to provide our buildings with an environmental adaptation offers some advantages in traditional construction, since some lessons in sustainable Mediterranean architecture underlie it and these may lead to interventions of revitalization of these areas.